Unediting Deor - Brljak, Vladimir (Array, 2011)
The article reviews editorial and critical work on the Old English poem Deor. Starting from the long-standing cruces of the poem’s third section and moving on to broad interpretive issues, it argues that Deor is an original vernacular take on the de casibus genre, employing a series of interconnected native exempla from the so-called Theodoric cycle as illustrations of stock medieval themes of the fickleness of fortune and the transience of mortal existence. Finally, the article makes a plea for further inquiry into the remaining philological problems of this poem.